Hubungan antara Volume Intracerebral Hemorrhage dan Derajat Midline Shift terhadap Tingkat Kesadaran Menurut Glasgow Coma Scale di Rumah Sakit (RS) Siti Khodijah Muhammadiyah Sepanjang - Mahendra, Raditya Bayu; Putra, Muslim Andala; Hamdzi, Muhammad Azharul; Irfana, Laily; Mochtar, Nur Mujaddidah (Universitas Batanghari Jambi, 2025)
The aim of this study was to determine the relationship between the volume of intracerebral hemorrhage (ICH) and the degree of midline shift with the level of consciousness according to the Glasgow Coma Scale at Siti Khodijah Muhammadiyah Panjang Hospital. ICH and midline shift data were collected from medical records, and ICH and midline shift measurements were carried out by 3 (three) radiology specialists, then the results of the medical records were linked using the Spearmen's correlation test. The results of the study found that there was a significant relationship between the volume of intracerebral hemorrhage (ICH) and the degree of midline shift on the Glasgow Coma Scale at the Siti Khodijah Muhammadiyah Panjang Hospital.